The 3rd World Conference on Kisspeptin, "Kisspeptin 2017: Brain and Beyond": Unresolved questions, challenges and future directions for the field. (20th May 2018) - Lehman, M. N.; Coolen, L. M.; Steiner, R. A.; Neal‐Perry, G.; Wang, L.; Moenter, S. M.; Moore, A. M.; Goodman, R. L.; Yeo, S.‐H.; Padilla, S. L.; Kauffman, A. S.; Garcia, J.; et al.
Abstract : The 3rd World Conference on Kisspeptin, "Kisspeptin 2017: Brain and Beyond" was held on 30‐31 March at the Rosen Centre Hotel in Orlando, Florida, providing an international forum for multidisciplinary scientists to meet and share cutting‐edge research on kisspeptin biology and its relevance to human health and disease. The meeting built upon previous world conferences focused on the role of kisspeptin and associated peptides in the control of gonadotrophin‐releasing hormone (GnRH) secretion and reproduction. Based on recent discoveries, the scope of this meeting was expanded to include functions of kisspeptin and related peptides in other physiological systems, including energy homeostasis, pregnancy, ovarian and uterine function, and thermoregulation. In addition, discussions addressed the translation of basic knowledge of kisspeptin biology to the treatment of disease, with the goal of seeking consensus about the best approaches to improve human health. The 2‐day meeting featured a nontraditional structure, with each day starting with poster sessions followed by lunch discussions and facilitated large‐group sessions with short presentations to maximise the exchange of new, unpublished data. Topics were identified by a survey prior to the meeting, and focused on major unresolved questions, important controversies and future directions in the field. Finally, career development activities provided mentoring for trainees and junior investigators, as well as networking opportunities for those individuals with established researchers in the field. Overall, the meeting was rated as a success by attendees and covered a wide range of lively and provocative discussion topics on the changing nature of the field of "kisspeptinology" and its future.